HETEROGENITY OF PRIMARY BLOOD HYPERTENSION RISK FACTORS IN CHILDREN AND ADOLESCENTS - O.L. Kolobova (Педиатрическая фармакология)
The development of diagnostic and treatment methods used for blood hypertension and its’ complications is a crucial concern of pediatrics. The study included 229 children, the study group consisted of 113 children (60 boys, 53 girls) with elevated blood pressure, the control group consisted of 116 children (60 boys, 56 girls). The age ranged between 6 and 17 years. The study investigated the following genetic markers of blood hypertension angiotensin converting enzyme gene(ace) I/D polymorphism, angiotensin G 6 A gene polymorphism, type I receptor to angiotensin II a 1166 C gene polymorphism, apolyprotein E (APOE) gene polymorphism, TRP 64 ARG β3-adrenoreceptor, C 677 T MTHFR gene polymorphism. Statistically significant increase of I allele of polymorhous i/d marker of ace gene and 677 T MTHFR gene has been observed in patients with primary blood hypertension when compared with the controls. Correlation between total cholesterol and LDLP cholesterol levels has been strong in patients with primary blood hypertension regardless to sex, age and familial history.Key words: primary blood hypertension, genetic markers, correlation analysis.